1997
DOI: 10.1016/s0025-6196(11)63565-9
|View full text |Cite
|
Sign up to set email alerts
|

A New Autosomal Dominant Disorder of Pyogenic Sterile Arthritis, Pyoderma Gangrenosum, and Acne: PAPA Syndrome

Abstract: The acronym of PAPA syndrome (pyogenic sterile arthritis, pyoderma gangrenosum, and acne) is suggested for this newly recognized pleiotropic autosomal dominant disorder. The nature of the genetic alteration in PAPA syndrome is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(135 citation statements)
references
References 12 publications
0
132
1
2
Order By: Relevance
“…Reports from the literature suggest that corticosteroids are beneficial for arthritis but less effective in pyoderma gangrenosum 5153. Immunosuppressants are partially effective at best, although the combination of sulfasalazine and leflunomide induced remission in one reported case 52 53.…”
Section: Resultsmentioning
confidence: 95%
“…Reports from the literature suggest that corticosteroids are beneficial for arthritis but less effective in pyoderma gangrenosum 5153. Immunosuppressants are partially effective at best, although the combination of sulfasalazine and leflunomide induced remission in one reported case 52 53.…”
Section: Resultsmentioning
confidence: 95%
“…A related autoinflammatory condition is the PAPA syndrome (pyogenic arthritis, pyoderma gangrenosum and acne), which shares overlapping features with PsA, including monoarthropathy and pustular skin disease 23. Collectively these clinical manifestations strongly overlap with inflammatory bowel disease and PsA phenotypes 24.…”
Section: Understanding the Genetics Of The Pathogenesis Of Psoriatic mentioning
confidence: 99%
“…68 A recent study in this regard found subclinical enthesopathy in over 40% of psoriasis cases69 and similar findings have been demonstrated with MRI,70 observations that support the deep Koebnerisation response. Not surprisingly the monogenic disorders of innate immunity and the PAPA syndrome, in particular, have been associated with trauma as a precipitating factor,23 24 71 which collectively suggests that microdamage is a pivotal factor in any array of inflammatory arthropathies related to the SpA spectrum.…”
Section: Subclinical Skeletal Abnormalities In Psoriasismentioning
confidence: 99%
“…PAPA syndrome is a rare autosomal dominant condition first described in 1997 in a large American pedigree where 10 family members over three generations showed variable expression of pauciarticular, non-axial, destructive, corticosteroid responsive arthritis that began in childhood, pyoderma gangrenosum and severe cystic acne in adolescence and beyond 11. Since then there have been a number of other case reports and the involved gene has been identified as PSTPIP1 (also known as CD2BP1), although the exact function of the gene product is as yet not fully understood 12.…”
Section: Commentmentioning
confidence: 99%